The Effect of Aging on Memory for Recent and Remote Egocentric and Allocentric Information. Issue 1 (1st January 2019) - Lopez, Antonella; O. Caffò, Alessandro; Spano, Giuseppina; Bosco, Andrea
ABSTRACT: Background : The present study explores recent and well-consolidated spatial memory within the egocentric and allocentric frames of reference in young and elderly people. Methods : The research included young and old participants, within the range of normality. All the participants were tested on four spatial tasks requiring allocentric and egocentric judgments, based on recent as well as remote spatial information, using a Multivariate Regression Analysis. Results : An age effect on both egocentric and allocentric tasks was present in recently learned spatial information. The age effect was not present in tasks regarding well-consolidated spatial information. Finally, sex influenced the performance in allocentric tasks regarding both recent and well-consolidated memory. Conclusion : These data were discussed according to the Multiple Trace Theory, supporting the idea that the magnitude of difference between egocentric and allocentric judgments in aging is somewhat attributable to the characteristic of spatial tasks. In general, a lower difference between the performance of young and elderly participants is shown in tasks based on well-consolidated information when compared with tasks based on episodic information. Well-consolidated information seemed to be better preserved in memory and less prone to the impairment.